Respuesta :
Answer:
y = 4/3
Step-by-step explanation:
I am going to assume you mean what y is equal to in this equation, so I will solve for y.
Equation: -3y - (-10) = 6
The first step to solving this is getting rid of -10. In order to do this, you need to subtract 10 from both sides.
3y + 10 - 10 = 6 - 10
This leaves us with 3y = -4.
To finally solve this equation, you will need to divide both sides by 3:
3y ÷ 3 = -4 ÷ 3
For the first half, 3 cancels itself out leaving us with y.
For the second half, dividing -4 by 3 leaves us with the fraction 4/3.
This means our equation is now y = 4/3, giving us the answer.
This answer can be checked by plugging in 4/3 and solving the equation